2020
DOI: 10.12700/aph.17.9.2020.9.4
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Cybersecurity Framework in the Road Transportation Domain

Abstract: The Automotive Industry has advanced significantly and this process is constantly continuing. Cars are controlled by hundreds of electrical units, which affects directly numberless safety and security related risk factors, especially considering incidents realized in the cyberspace. Due to the increasing number of connected cars, new testing facilities and methods need to be established, to support the solutions, for these novel challenges. For this reason, the Hungarian government has founded the Zalaegerszeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Cooperative Intelligent Transportation System (C-ITS) communication among vehicles (V2V), infrastructure (V2I and I2V) and central traffic system (C2I) is also a significant factor to consider in improving the operation of highly automated vehicles [18,19]. V2X communications proved that it could provide local traffic flow stability, significantly smoothen the shock waves of traffic flow and reduce emissions [20,21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cooperative Intelligent Transportation System (C-ITS) communication among vehicles (V2V), infrastructure (V2I and I2V) and central traffic system (C2I) is also a significant factor to consider in improving the operation of highly automated vehicles [18,19]. V2X communications proved that it could provide local traffic flow stability, significantly smoothen the shock waves of traffic flow and reduce emissions [20,21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another aspect of eco-driving is using navigation systems to improve fuel consumption. The shortest or fastest route is not always the best choice in fuel consumption and emissions [14,39,40]. Ericsson et al's study found that 46% of driver-chosen journeys were not the most fuel-efficient routes, and using fuel-optimized navigation systems saved up to 8.2% in fuel consumption [41].…”
Section: Autonomous Vehicles(avs)mentioning
confidence: 99%